T’boli-Bla’an Dream Weaving: compare to Native Amercian The Sonenekuiñaji, The Parintintin, The Chipewyan (A Casale) & E Hill as "meaning construction" & social-spiritual self w/ dreaming as transcendence in divine grace,& guidance w/ divine inspiration + ... - Peck Jr, Charles (Humanities Commons, 2024)
“The craft of weaving among the T’boli is a sacred spiritual tradition. Designs are believed to arrive from Fu Dalu, the spirit of the Abaca [material for cloth] (p.214). T’boli people are known to be one of the most creative and artistic ethnolinguistic group in the Philippines (Cudera et al., 2020). Among the different T’boli art forms, T’nalak is one of the most popular and admired around the globe. T’nalak is a traditional hand-woven cloth indigenous to the T’boli people from the Cotabato region. It is woven in order to celebrate and pay tribute to major life events such as birth, life, marriage, or death within the community. The cloth is woven from abaca fibers and is naturally dyed from bark, roots, and certain plants. The fabric undergoes a unique tie-dye process where it is tied in specific knots measured by finger or knuckle length, and dipped in dyes in order to create ornate patterns that indicate precision in craftsmanship. This is denoted by a distinctive tri-color scheme; the background is ...